Iraq Early Childhood Development : SABER Country Report 2014 - Adams, Lindsay (World Bank, Washington, DC, 2018)
This report presents an analysis of the early childhood development (ECD) programs and policies that affect young children in Iraq and recommendations to move forward. This report is part of a series of reports prepared by the World Bank using the Systems Approach for Better Education Results–Early childhood development (SABERECD) framework and includes analysis of early learning, health, nutrition, social protection, and child protection policies and interventions in Iraq, along with regional and international comparisons.